(3GdahGcg GdLfjI Ydi TQM GdCLQhejI dNGdO GdCRgQjs - (3GdbdjhHj GdCRgQj, CHh GdYHGS, TgGH GdOjf, CMeO Hf CMeO Hf SdGeI, (B1069 (3g`s
(3ChdgG (B:s
(3hHg KbJj GdMeO ddg GdPj QaY ebGe ef fUH faSg dfaY GdYHGO hGdUdGI hGdSdGe Ydi ef LRe HNaV ebGe Cgd GdLgd hGdYfGOs
(3BNQgG (B:s
(3GdeSei Cj GdGSe Ch EVGaI eG Hjfg hHjf eVGag Yehe ef hLg CbhGd KdGKI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 92s
(3eYLe GdeDdajf(B: 1 / 94s
(3cTa GdXfhf(B: 2 / 1797s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs